2021
DOI: 10.1016/j.gore.2021.100883
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted MRI to detect early response to chemoradiation in cervical cancer: A systematic review and meta-analysis

Abstract: Highlights DWI has potential as a non-invasive biomarker of early treatment response in patients with cervical cancer. A change in ADC seen early in a therapy regime significantly correlated with eventual response. Further studies are required to determine an ideal cut-off or range of ADC values that can be used to predict response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…Numerous studies have adopted ADC values in the prognosis of cervical cancer [ 42 ]; however, only some studies reported histogram-derived ADC maps in cervical cancer. An ADC value is influenced by molecular viscosity, membrane permeability, and cell structures, and histogram-derived parameters based on ADC values reflect cell heterogeneity in different physiological states.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have adopted ADC values in the prognosis of cervical cancer [ 42 ]; however, only some studies reported histogram-derived ADC maps in cervical cancer. An ADC value is influenced by molecular viscosity, membrane permeability, and cell structures, and histogram-derived parameters based on ADC values reflect cell heterogeneity in different physiological states.…”
Section: Discussionmentioning
confidence: 99%
“…4 Based on this revised classification, cross-sectional imaging, especially magnetic resonance imaging (MRI), has a crucial role in determining cervical cancer staging. 3,4,6,[17][18][19] MRI can determine the origin of the mass, the size of the masses more accurately, invasion of the parametrium, pelvic wall, vagina, bladder, ureter, and rectum, and see the presence of lymph node involvement. 5,17,18 In our study, we highlight the importance of T2WI and DWI-ADC sequences in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study by Law et al (2016) In addition, DWI can provide information on the timing and extent of treatment response, allowing for early modification of treatment plans if necessary. A study by Harry VN et al (2021) found that DWI was able to detect treatment response as early as 2 weeks after the start of chemoradiotherapy, and was able to predict treatment response with high accuracy. (Harry VN, Persad S, Bassaw B & Parkin D., 2021) Overall, DWI has the potential to play an important role in radiation therapy planning and treatment monitoring for Nasopharyngeal carcinoma patients, and may ultimately improve treatment outcomes and quality of life for these patients.…”
Section: Potential Applications Of Diffusion-weighted Imaging In Radi...mentioning
confidence: 99%